ESTUDO DA DISTRIBUIÃ‡ÃƒO DA ð˜‹ð˜ð˜ˆð˜›ð˜™ð˜ˆð˜Œð˜ˆ ð˜šð˜ˆð˜Šð˜Šð˜ð˜ˆð˜™ð˜ˆð˜“ð˜ð˜š F. NO TALHÃƒO DE CANA-DE-AÃ‡ÃšCAR - Moraes, Gilberto JosÃ©; Berti Filho, EvÃ´neo; Gallo, Domingos (REVISTA DE AGRICULTURA, 2020)
ESTUDO DA DISTRIBUIÃ‡ÃƒO DA ð˜‹ð˜ð˜ˆð˜›ð˜™ð˜ˆð˜Œð˜ˆ ð˜šð˜ˆð˜Šð˜Šð˜ð˜ˆð˜™ð˜ˆð˜“ð˜ð˜š F. NO TALHÃƒO DE CANA-DE-AÃ‡ÃšCAR